(untitled) (British Journal of Global Ecology and Sustainable Development, 2025)
This article examines the correlation between economic traits and biochemical parameters of selected rice (Oryza sativa L.) varieties cultivated under the conditions of the Andijan region. Furthermore, the obtained results were comparatively analyzed with similar research conducted by scientists worldwide, and it was emphasized that the economic and biochemical parameters of rice varieties hold significant scientific importance in breeding and variety identification practices.